The Russia–Ukraine Conflict: Nepal’s Foreign Policy in New Dimension of World Power - Lamsal, Hiranya Lal (Unity Journal, 2023)
How can Nepal engage with big powers? To do so, what kind of foreign policy should Nepal adopt? These questions are the main concerns of the study. In the present world scenario, foreign policy requires building a rapport with other countries Any country would need distinctive foreign policies to ensure national security, territorial integrity, and the protection of people’sovereignty. This study aims at exploring Nepal’s foreign policy in light of the ongoing Russia–Ukraine conflict. It follows an interpretative research design. It uses an inductive, qualitative method of study, collecting secondary data in the form of expert interviews, content-specific thematic analysis to construct a specific set of themes about the Russia-Ukraine conflict. The paper unfolds how foreign policy safeguards the territorial integrity of a country and protects the interest of its citizens, both within and outside the country. It has exemplified Ukraine’s situation as a reminder to small powers so that they tread a fine line in balancing between the preservation of sovereignty and signifying strategic empathy towards the interests of major powers.